MEDICATION COMPLIANCE AND THE ROLE OF MEDICATION SUPERVISOR BASED ON THE PERCEPTION OF TUBERCULOSIS PATIENTS: A DESCRIPTIVE STUDY - Wulan, Dinarsih Ayuning; Sofiana, Liena; Oktaviana, Ardyawati Wira (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2026)
Background: The success of tuberculosis (TB) treatment largely depends on patient adherent to Anti-Tuberculosis Drugs. Medication supervisors play a crucial role in supporting adherence through the Directly Observed Treatment Short course. Purpose: This study aims to describe medication adherence and the role of medication supervisors based on TB patients’ perceptions. Methods: This descriptive quantitative study involved a population of 35 tuberculosis patients undergoing treatment at Depok III Health Center (27 cases) and Godean I Health Center (8 cases) from May to October 2023. A total of 31 patients with consent were included as respondents using a total sampling technique. Data on medication adherence and perceptions of the role of medication supervisors were collected through a structured questionnaire tested for validity and reliability, then analyzed descriptively. Results: The majority of respondents were male, aged 15–39 years and demonstrated a high level of medication adherence (96.8%). Respondents perceived medication supervisors as effective in reminding them to take medication and explaining treatment procedures, but less optimal in providing direct assistance, family education, and information about side effects. Conclusion: Medication adherence among TB patients in the study area was high. However, the role of medication supervisors needs to be strengthened in direct assistance, family education, and side effect management. Capacity building through structured training and supervision is required to increase the success of TB treatment.